Synthesis and desalination performance of Ar+-N+ irradiated polysulfone based new NF membrane - Chitrakara Hegde (2018)
In the last few years, membrane technology has gained more attention from polymer chemists throughout the globe. Nowadays, surface modification of membrane is very useful in biotechnology and food science. In the present investigation, we have synthesized polysulfone based composite nanofiltration (NF) membranes, and characterized these membranes by FT-IR, SEM and membrane performance studies. Surface plasma treatment was carried out by irradiation with argon and nitrogen beams in suitable conditions. It was observed that nitrogen beam caused surface roughness that was more severe than the Ar beam. After irradiation, water contact angle was slightly increased. For pure water permeability, flux increased linearly with the operating pressure. However, for the salt solution, the flux was decreased marginally and salt rejection increased after irradiation due to surface modification. The modification effect was characterized in terms of contact angle, AFM employed roughness measurement and dielectric property. It revealed that irradiated NF membranes showed higher salt rejection and lower flux as compared to the nonmodified membranes. Accordingly, the roughness of the membrane surface intensively affected the performance of RO membrane. © 2010 Elsevier B.V.